KEBIJAKAN PENANGGULANGAN KRISIS EKONOMI DAN KONSEKUENSINYA TERHAPAP PELUANG PENINGKATAN PENDAPATAN PETANI - BAMBANG IRAWAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2002)
Economic crisis and various economic recovery policies issued by government lead tomore dynamic and fluctuative prices of foodstuffs and agricultural inputs since mid 1997.During the peak period of the crisis food prices at retail market increased at higher rate, about3 to 25 times of price growth before crisis, particularly for the low price foodstuffs. Thismeans that the crisis tends to cause higher impact on food consumption of low incomehousehold. To overcome the crisis various trade policies on food and agricultural inputsissued by government so that the rate of growth of food prices become lower, in other word,favorable for food consumer. Those policies however were unfavorable for farmer’s incomeincrease because due to policies on inputs trade the ratio of food prices to inputs pricesdecreased with increasing rate. The situation was more difficult for future agriculturedevelopment, which more focused on income increse instead of production increase, becausein addition to unfavorable prices the crisis also lead to increase of number of people involvedin agricultural sector about 3.56 million people or 9.9 persen. In order to support agriculturedevelopment, accordingly, reorientation and reorganisation of food trade policies for riceparticularly is required.